Low-Intensity Blue Light Supplemented during Photoperiod in Controlled Environment Induces Flowering and Antioxidant Production in Kalanchoe - Jingli Yang; Jinnan Song; Byoung Ryong Jeong (MDPI AG, 2022)
Kalanchoe (Kalanchoe blossfeldiana) is a qualitative short-day plant with a high aesthetic value. When the night length is less than a specified cultivar-dependent critical value, however, it does not develop flowers. This study investigated the effects of low-intensity supplementary or night interrupting (NI) blue (B) light on the plant performance and flower induction in kalanchoe 'Rudak'. During the photoperiod in a closed-type plant factory with day/night temperatures of 23 °C/18 °C, white (W) LEDs were utilized to produce a photosynthetic photon flux density (PPFD) of 300 μmol m−2 s−1, and B LEDs were used to give supplementary/NI light at a PPFD of 10 μmol m−2 s−1. The control plants were exposed to a 10-h short day (SD, positive control) or a 13-h long day (LD, negative control) treatment without any B light. The B light was used for 4 h either (1) to supplement the W LEDs at the end of the SD (SD + 4B) and LD (LD + 4B), or (2) to provide night interruption (NI) in the SD (SD + NI-4B) and LD (LD + NI-4B). The LD + 4B and LD + NI-4B significantly enhanced plant growth and development, followed by the SD + 4B and SD + NI-4B treatments. In addition, the photosynthesis, physiological parameters, and activity of antioxidant systems were improved in those treatments. Except in the LD and LD + NI-4B, all plants flowered. It is noteworthy that kalanchoe 'Rudak' flowered in the LD + 4B treatment and induced the greatest number of flowers, followed by SD + NI-4B and SD + 4B. Plants grown in the LD + 4B treatment had the highest expression levels of certain monitored genes related to flowering. The results indicate that a 4-h supplementation of B light during the photoperiod in both the SD and LD treatments increased flower bud formation, promoted flowering, and enhanced plant performance. Kalanchoe 'Rudak' flowered especially well in the LD + 4B, presenting a possibility of practically inducing flowering in long-day seasons with B light application.